Fluorinated nitrile-butadiene rubber (F-NBR) via metathesis degradation: Closed system or open system?. (5th January 2022) - Pan, Changou; Liu, Peng
Graphical abstract: Highlights: F-NBR was prepared via the metathesis degradation of NBR in the closed system. It was greener and more efficient than that in the open system. It was suppressed due to the reaction equilibrium with F6 as F-CTA. It was promoted due to pressure-enhanced miscibility and ethenolysis with F13. Abstract: Fluorinated nitrile-butadiene rubber (F-NBR) could be designed via the metathesis degradation of nitrile-butadiene rubber (NBR) with perfluoroalkylethyl acrylates as fluorination chain transfer agent (F-CTA). Ethylene was produced during the metathesis degradation. Different from the reported works in the open system in which the ethylene escaped, the reaction in a closed system is greener. Here, the metathesis degradation of NBR was investigated in a closed system for the first time, with 2, 2, 3, 4, 4, 4-hexafluorobutyl acrylate (F6) or 1H, 1H, 2H, 2H-perfluorooctyl acrylate (F13) as F-CTA, respectively. Compared with the reaction in the open system, the metathesis degradation in the closed system with F6 was suppressed due to the reaction equilibrium, while that with F13 was promoted owing to the ethenolysis reaction, which was caused by the ethylene produced during the metathesis degradation. With the proposed green and efficient approach, the fluorinated liquid nitrile-butadiene rubber (F-LNBR) could be designed for various applications.